Fiscal Policy Response to External Crises the Case of Moldova 1998-2010 - Qehaja, Driton (IMF Working Papers; Working Paper, 2012)
External shocks pose major challenges to fiscal policy makers through lower output and large fiscal imbalances. This paper analyzes the case of Moldova, which faced parallel crises a decade apart: the Russian crisis of 1998 and the global financial crisis of 2008-2009. The country went through large fiscal adjustments during these crises and launched important fiscal reforms. The paper reviews the crises and reform experience. In particular, it aims to explain the motivation for reforms, describe reform design and implementation, and provide an understanding of their outcomes. The paper also catalogues the form and size of international assistance for Moldova.